The Effect of Picture Media to Improve Forward Roll Ability - Dila Wasilah; Anggi Setia Lengkana; Entan Saptani (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
This study aims to determine the effect of applying visual (image) media on improving the forward roll ability of fifth-grade students at Cibungur State Elementary School. The research used a quantitative approach with a pre-experimental design one-group pretest–posttest design. The research subjects consisted of 35 students selected using total sampling. The instrument used was a forward roll skill test based on movement indicators, including initial position, hand and foot position, rolling process, and final position, validated through expert judgment with high reliability (Cronbach’s Alpha = 0.86; ICC = 0.90). Data were analyzed using descriptive statistics and paired sample t-test. The results showed a significant increase in students' abilities, with the average score rising from 50.49 (pretest) to 96.40 (posttest), and a gain score of 45 points. The t-test results indicated a significance value of p < 0.05, confirming that the improvement was statistically significant. In addition, the decrease in standard deviation indicated a more homogeneous distribution of student abilities after the intervention. These findings suggest that visual media is effective in improving students' forward roll skills by providing clear and systematic movement visualization. Therefore, visual media can be recommended as an innovative and effective learning strategy in physical education study.